2012
DOI: 10.1002/chem.201102651
|View full text |Cite
|
Sign up to set email alerts
|

A New Ammine Dual‐Cation (Li, Mg) Borohydride: Synthesis, Structure, and Dehydrogenation Enhancement

Abstract: A new ammine dual-cation borohydride, LiMg(BH(4))(3)(NH(3))(2), has been successfully synthesized simply by ball-milling of Mg(BH(4))(2) and LiBH(4)·NH(3). Structure analysis of the synthesized LiMg(BH(4))(3)(NH(3))(2) revealed that it crystallized in the space group P6(3) (no. 173) with lattice parameters of a=b=8.0002(1) Å, c=8.4276(1) Å, α=β=90°, and γ=120° at 50 °C. A three-dimensional architecture is built up through corner-connecting BH(4) units. Strong N-H···H-B dihydrogen bonds exist between the NH(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 59 publications
5
72
1
Order By: Relevance
“…23, 33 Among these AMBs, As reported in a previous literature study, [Zn(NH 3 ) 2 ][BH 4 ] 2 is able to release 8.9 wt% hydrogen below 115 o C within 15 min without concomitant release of undesirable gases such as ammonia and boranes. 22The dehydrogenation of some of the AMBs may be achieved through combining hydrides from [BH 4 ]and protons from NH 3 , ultimately yielding amorphous metal boronitrides 19,[23][24][25][26][34][35][36]. The experimental observation of the formation of well-crystallized Zn during…”
mentioning
confidence: 99%
“…23, 33 Among these AMBs, As reported in a previous literature study, [Zn(NH 3 ) 2 ][BH 4 ] 2 is able to release 8.9 wt% hydrogen below 115 o C within 15 min without concomitant release of undesirable gases such as ammonia and boranes. 22The dehydrogenation of some of the AMBs may be achieved through combining hydrides from [BH 4 ]and protons from NH 3 , ultimately yielding amorphous metal boronitrides 19,[23][24][25][26][34][35][36]. The experimental observation of the formation of well-crystallized Zn during…”
mentioning
confidence: 99%
“…a) MS and b) TG profiles of Zr(BH 4 ) 4 ·8NH 3 -n LiBH 4 (n = 0, 2, 4) at aheating rate of 5 8Cmin À1 underana tmosphereofargon.c)Isothermal dehydrogenation data for Zr(BH 4 ) 4 ·8NH 3 -4 LiBH 4 at various temperatures. [8,11] In addition, it has been reported that DADB was formed on the decomposition of Cr(BH 4 ) 3 ·6NH 3 . [12] Hence, it was assumed that ad ual-cation (Li, Zr) borohydridea mmoniate was first formed by the combination of Zr(BH 4 ) 4 ·8NH 3 andL iBH 4 ,w hicht hen could decompose with formationofD ADB as an intermediate.…”
Section: Dehydrogenation Properties Of Zr(bh 4 ) 4 ·8 Nh 3 -N Mg(bh 4mentioning
confidence: 99%
“…The conversion of BH 4 into a sp 2 boron species in PSDB-confined Al(BH 4 ) 3 ·6 NH 3 occurred at lower temperatures than for other MBAs; for those, a temperature greater than 300 8C is required to completely consume the BH groups. [14] Motivated by recent examples of the use of hydrazine for the regeneration of dehydrogenated residues of BÀN based hydrides (such as ammonia-borane [15] and lithium amidoborane [16] ), we implemented the same approach for Al(BH 4 ) 3 ·6 NH 3 . After treatment with hydrazine in liquid ammonia, the 11 B NMR signals of decomposed residues of Al(BH 4 ) 3 ·6 NH 3 /PSDB diminished; this was accompanied by the appearance of a broad resonance at 0-30 ppm that corresponds to the superimposition of the BH, BH 2 , and BH 3 signals (Figure 5 a).…”
Section: [5a]mentioning
confidence: 99%